Great Transformations: Economic Ideas and Institutional Change in the Twentieth Century - Blyth, Mark (Cambridge University Press, 2002)
Mark Blyth argues that economic ideas are powerful political tools as used by domestic groups in order to effect change since whoever defines what the economy is, what is wrong with it, and what would improve it, has a profound political resource in their possession. Blyth analyzes the 1930s and 1970s, two periods of deep-seated institutional change that characterized the twentieth century. Viewing both periods of change as part of the same dynamic, Blyth argues that the 1930s labor reacted against the exigencies of the market and demanded state action to mitigate the market's effects by "embedding liberalism" and the 1970s, those who benefited least from such "embedding" institutions, namely business, reacted against these constraints and sought to overturn that institutional order. In Great Transformations, Blyth demonstrates the critical role economic ideas played in making institutional change possible and he rethinks the relationship between uncertainty, ideas, and interests on how, and under what conditions, institutional change takes place. Mark Blyth is an assistant professor of political science at the Johns Hopkins University specializing in comparative political economy. He has taught at Columbia University, and at the University of Birmingham, UK. Blyth is a member of the editorial board of the Review of International Political Economy.
Political Science
Keywords: economic policy; political economy; political science; public policy

Chronik der grossen Transformation. Artikel und Aufsätze (1920-1945) / Wirtschaftliche Transformation, Gegenbewegung und der Kampf um die Demokratie - Cangiani, Michele; Thomasberger, Claus; Polanyi, Karl (Metropolis, 2002)
ENGLISH: In the last few years the interest in Karl Polanyi's work has been growing between 1920 and 1945, and with only a few exceptions they are difficult or impossible to access. The articles, essays, and manuscripts written in Vienna and England are not only the result of intensive studies during the central years of the author's life, but they are also the main part of his work. In this work, Polanyi analyzes a period decisive for the development of the twentieth century. The writings deal not only with the central problems and questions, the results of which are incorporated in his main work, The Great Transformation, published in 1944, without giving any further explicit insight, and thus provide an insight into the ideas, ideas, and reflections from which they emerged are. They are also (and above all) important time documents, significant as direct and immediate reflections on the political and economic events of the inter-war period. Polanyi analyzes with great care both the economic and political events, the global economic crisis as well as the international political situation, the attempts to create the conditions for peace and recovery, as well as the conflicts that point towards a new world war. The main topics for the Austrian economist include industrial restructuring, corporate tendencies, the rise of fascism and the transformation of the economic and political institutions in Great Britain and the USA during the New Deal period. These are supplemented by works on fundamental topics such as pricing, economic theory, sociology and the theory of socialism. All investigations are subject to a uniform, theoretically and politically fundamental question: How can - after the collapse of the liberal system of the 19th century such as the socialist hopes of the twenties - defend and expand democracy and freedom? The most important articles, essays and manuscripts, which were written in the period between 1920 and 1945, are grouped into three volumes according to their content. Volume I, entitled Economic Transformation, Counter-Movements and the Fight for Democracy, contains the analyzes on the areas of economy, global economic crisis and economic policy. The subject of Volume II is The international policy between the two world wars. Volume III, in which we have summarized the theoretical work on pricing, socialist economic analysis, Marxism, sociological theory, socialism, and democracy, is under the heading of freedom, democracy, and socialism. DEUTSCH: In den letzten Jahren wächst das Interesse an den Arbeiten, die Karl Polanyi zwischen 1920 und 1945 verfasste und die - mit wenigen Ausnahmen - bisher nur schwer oder gar nicht zugänglich sind. Die in Wien und in England geschriebenen Artikel, Aufsätze und Manuskripte sind nicht nur das Ergebnis intensiver Studien während der zentralen Jahre des Lebens des Autors, sie machen auch den Hauptteil seines Werkes aus. Polanyi analysiert in diesen Arbeiten eine für die Entwicklung des zwanzigsten Jahrhunderts entscheidende Periode. Die Schriften behandeln nicht nur die zentralen Problem- und Fragestellungen, deren Resultate, ohne erneut explizit aufgegriffen zu werden, in seinem 1944 publizierten Hauptwerk, The Great Transformation, einfließen, und geben damit Einblick in die Gedankengänge, Ideen und Überlegungen, aus denen jene hervorgegangen sind. Sie sind auch (und vor allen Dingen) wichtige Zeitdokumente, bedeutsam als direkte und unmittelbare Reflexionen über die politischen und wirtschaftlichen Ereignisse der Zwischenkriegsphase. Polanyi analysiert mit großer Sorgfalt sowohl die wirtschaftlichen wie auch die politischen Ereignisse, die Weltwirtschaftskrise wie die internationale politische Lage, die Versuche, die Bedingungen für Frieden und Aufschwung herzustellen, wie die Konflikte, die in Richtung eines neuen Weltkriegs weisen. Zu den Themen der hauptsächlich für den Österreichischen Volkswirt verfassten Artikel gehören die industrielle Restrukturierung, die korporativen Tendenzen, der Aufstieg des Faschismus sowie die Transformation der ökonomischen und politischen Institutionen in Großbritannien und in den USA während der Periode des New Deal. Diese werden ergänzt durch Arbeiten über grundsätzliche Themen wie Preisbildung, ökonomische Theorie, Soziologie und Theorie des Sozialismus. Allen Untersuchungen unterliegt eine einheitliche, theoretisch und politisch grundlegende Fragestellung: Wie können - nach dem Zusammenbruch des liberalen Systems des 19. Jahrhunderts wie der sozialistischen Hoffnungen der zwanziger Jahre - Demokratie und Freiheit verteidigt und ausgebaut werden?Die wichtigsten Artikel, Aufsätze und Manuskripte, die in der Periode zwischen 1920 und 1945 entstanden sind, werden nach inhaltlichen Schwerpunkten in drei Bände gruppiert. Band I, der die Überschrift Wirtschaftliche Transformation, Gegenbewegungen und der Kampf um die Demokratie trägt, enthält die Analysen zu den Themenbereichen Wirtschaft, Weltwirtschaftskrise und Wirtschaftspolitik. Gegenstand von Band II ist Die internationale Politik zwischen den beiden Weltkriegen. Band III, in dem wir die theoretischen Arbeiten zur den Fragen Preisbildung, sozialistische Wirtschaftsrechnung, Marxismus, soziologische Theorie, Sozialismus und Demokratie u.a. zusammengefasst haben, steht unter der Überschrift Freiheit, Demokratie und Sozialismus. InhaltMichele Cangiani und Claus ThomasbergerVorbemerkung9Marktgesellschaft und Demokratie: die Perspektive der menschlichen Freiheit. Karl Polanyis Arbeiten von 1920 bis 1945 11I.Politische Kämpfe in den zwanziger Jahren1.England und die Wahlen 462.Zur Krise der englischen Arbeiterbewegung513.Die neue Internationale564.Das Bergbauproblem in England635.Der englische Generalstreik726.Probleme des englischen Generalstreiks80II. Liberale Reformprojekte7.Liberale Wirtschaftsreformen in England908.Liberale Sozialreformer in England959.Schmalenbach und Liberalismus104III.Die Weltwirtschaftskrise10.Zur wirtschaftlichen Neuordnung Europas11011.Demokratie und Währung in England12012.MacDonald und die Wirtschaftspolitik12913.England auf der Waage13414.Kritik an Lausanne14215.Wirtschaft und Demokratie 14916.Weltinflationismus15517.Von Lausanne bis Washington16318.Brain-Trust siegt17019.Roosevelt zerschlägt die Konferenz178IV.Der Zusammenbruch der Demokratie in Deutschland und in Europa20.Gegenrevolution18621.Staatsgründung19322.Hitler und die Wirtschaft19923.Korporatives Österreich - eine funktionale Gesellschaft ?204V.Restrukturierung und Demokratie in England24.Wirtschaftsprogramm der Samuel-Liberalen21425.Ende der Slums21626.Englisches Stahlstatut21827.Technologische Arbeitslosigkeit22028.Elliot oder Empire ?22329.Probleme der Demokratie in England22630.Lohntarif-Bill in Lancashire22831.Lancashire im Fegefeuer23032.Lancashire als Menschheitsfrage23633.England überlegt24934.Labour und die Eisenindustrie25135.Gewerkschaftstagung in Weymouth25336.Labour in Southport25637.Tory-Planwirtschafter25938.Die Liberalen für Empirehandel261VI.New Deal39.Roosevelt im Verfassungskampf26440.Amerika im Schmelztiegel27141.Roosevelt im Kampf27942.T.V.A. - Ein amerikanisches Wirtschaftsexperiment28143.Arbeitsrecht in U.S.A.29044.Amerikanisches Gewerkschaftsgesetz verfassungsmäßig29145.Roosevelts strategischer Rückzug29346.Gewerkschaften in den U.S.A.295VII.Die Entwicklung in der Sowjetunion47.Zweiter Fünfjahresplan abgebremst29848.Wo hält Sowjetrußland?30849.Russischer Verfassungswandel316
History
Keywords: Polanyi essays